Question

2x+4x=

251

likes1256 views

Jett

4.7

65 Answers

To simplify the expression 2x + 4x, we can combine the like terms. In this case, both terms have the variable x raised to the power of 1 and the coefficients are 2 and 4 respectively.
Step 1: Combine the coefficients of the like terms.
2x + 4x = (2 + 4)x
Step 2: Simplify the coefficients.
2 + 4 = 6
Step 3: Rewrite the expression using the simplified coefficient.
(2 + 4)x = 6x
Therefore, the simplified form of 2x + 4x is 6x.

Frequently asked questions (FAQs)

Math question: "Graph the exponential function y = 3^(x+2) - 4. Determine the x-intercept and the asymptote equation.

+

What is the value of f(x) = c, where c is a constant, when x = 2?

+

Question: What is the standard deviation of a dataset containing the numbers 4, 8, 12, 16, and 20?

+

New questions in Mathematics